Response of Tomato to Crude and Fine Phosphatic Fertilizers Integrated with Cattle Manure and Indole Acetic Acid - Khan, Qudrat Ullah; Intisar ud Din; Ahmad, Muhammad Adeel; Sibghatullah; Khan, Muhammad Parvaiz; Latif, Asif; Ahmad, Imran; Khan, Asghar Ali; Hassan, Syed Shahzaib; Muhammad Ammar (Indus Journal of Bioscience Research, 2024)
Phosphatic fertilizers are an integral part of crop cycle and are responsible for food production. But due to continuous increase in prizes of fertilizer over the years, the economics of the farmer is affected and there is a dire need to find the alternate. To investigate the response of tomato (Lycopersicum esculuntum L.) to crude phosphate rock (CPR), commercial phosphate fertilizer alone, or integrated with cattle manure (CM), and indole acetic acid (IAA) an experiment was conducted in pot culture with the factors IAA and inorganic and/or organic fertilizers. A number of flowers, root length, number of fruit per plant, fruit diameter, 5 fruit weight, and fruit yield were affected by treatments. Use of commercial single super phosphate along with cattle manure fortified with IAA produced better results for growth and yield of tomato. Crude phosphate rock applied along with cattle manure and IAA performed better compared to CPR alone. Soil pH, Bulk density, organic matter and extractable phosphorus were influenced by use of treatments. Inorganic phosphatic fertilizer integrated with organic amendments performed better than the application of inorganic fertilizers and crude phosphate rock alone. Hence, it may be concluded that the integrated use of inorganic phosphatic fertilizer with manure fortified with IAA enhanced both growth and yield of tomato and also improved the soil properties.